Research and design - Seivewright, Simon (Basics fashion design, 2012)
"Research is fundamental to the success of any design-related project and in Research and Design you will discover what research is, why it is so important and where to go for inspiration when developing concepts and themes for your own creative sketchbook. Research and Design crucially shows you how to maximize what you have learnt at the research stage by successfully illustrating, communicating and presenting your design work."--Page [4] of cover.